Real Time Polymerase Chain Reaction : Perangkat Diagnostic Alternatif untuk Melacak Virus Nipah (REAL TIME POLYMERASE CHAIN REACTION : AN ALTERNATIVE DIAGNOSTIC TOOL TO DETECT NIPAH VIRUS) - Sendow, Indrawati; Ratnawati, Atik; Adjid, Raden Mas Abdul; Saepulloh, Muharam (Jurnal Veteriner, 2014)
Nipah is a dangerous zoonotic disease with a high social, economical and psychological impact. Fruitbat Pteropus sp. is one of the nipah virus  reservoir host. As the virus is categorized as a dangerous zoonoticdisease that cause fatal in human, all works related to live virus should be conducted in a laboratory withBSL4 facilities. The detection of nipah virus using real time PCR to replace virus isolastion can thereforebe conducted in a laboratory without BSL4 facilities. The results was further  confirmed at referencelaboratory at   Australian Animal Health Laboratory ( AAHL) Geelong, Australia, indicated that nipahvirus can be detected in saliva of fruit bat P. vampyrus in Medan North Sumatera.
Keywords: Nipah virus, zoonosis, viral detection, Real Time PCR, fruitbats